2016
DOI: 10.1513/annalsats.201603-203oc
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort Echo-Time Magnetic Resonance Imaging Is a Sensitive Method for the Evaluation of Early Cystic Fibrosis Lung Disease

Abstract: Ultrashort echo-time MRI detected structural lung disease in very young patients with CF and provided imaging data that correlated well with CT. By quantifying early CF lung disease without using ionizing radiation, ultrashort echo-time MRI appears well suited for pediatric patients requiring longitudinal imaging for clinical care or research studies. Clinical Trial registered with www.clinicaltrials.gov (NCT01832519).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
69
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 58 publications
0
69
1
3
Order By: Relevance
“…Inter-observer and intra-observer agreement of the common CT scores has shown to be good to excellent [128,129]. Comparable reproducibility has also been found for MRI using CT or MR-specific adapted scoring systems in small numbers of studies [144,148]. For semiautomatic evaluation of bronchi dimension excellent inter-observer agreement has been found particularly for the bronchial lumen [151].…”
Section: Clinical Valuementioning
confidence: 83%
See 1 more Smart Citation
“…Inter-observer and intra-observer agreement of the common CT scores has shown to be good to excellent [128,129]. Comparable reproducibility has also been found for MRI using CT or MR-specific adapted scoring systems in small numbers of studies [144,148]. For semiautomatic evaluation of bronchi dimension excellent inter-observer agreement has been found particularly for the bronchial lumen [151].…”
Section: Clinical Valuementioning
confidence: 83%
“…MRI has no side effects by radiation enabling long-term surveillance of lung damage. The overall diagnostic performance by scores evaluation of MRI in direct comparison to CT is good to excellent [144][145][146] (Fig. 4).…”
Section: Imaging Characteristics Of Bronchiectasismentioning
confidence: 98%
“…A recent study demonstrated that the UTE signal–intensity measurements of the lung are reproducible and significantly correlated with computed tomography (CT) measures of emphysema and pulmonary function testing in human subjects with chronic obstructive pulmonary disease . Moreover, UTE proton MRI has been recently shown to have favorable comparison to CT findings of lung structural changes in subjects with evidence of cystic fibrosis (CF) …”
mentioning
confidence: 99%
“…Recently, ultrashort echo time (UTE) MRI with 3D radial k ‐space trajectories has shown promise in overcoming these obstacles. However, experience with 3D radial UTE chest MR is limited to animal models and small human studies, mostly in adults . Moreover, 3D radial acquisitions suffer from inherent inefficiencies in fully populating k ‐space, leading to trade‐offs between longer scan times and data undersampling with lesser resolution …”
mentioning
confidence: 99%
“…However, experience with 3D radial UTE chest MR is limited to animal models and small human studies, mostly in adults. [15][16][17][18][19][20][21][22][23] Moreover, 3D radial acquisitions suffer from inherent inefficiencies in fully populating k-space, leading to trade-offs between longer scan times and data undersampling with lesser resolution. 24 UTE imaging utilizing conical k-space sampling permits greater scan efficiency than do radial acquisitions.…”
mentioning
confidence: 99%